Were SARS-CoV-2 self-tests used for their intended purpose? The experience in Belgium - Yves Lafort; Laura Cornelissen; Dieter Van Cauteren; Barbara Verboven; Sabine Drieskens; Simon Couvreur; Lize Hermans; Koen Straetmans; Tinne Lernout (BMC, 2023)
Abstract Background Self-testing has been promoted as a means of increasing COVID-19 test coverage. In Belgium, self-testing was recommended as a complement to the formal, provider-administered indications, such as out of courtesy before meeting others and when feared to be infected. More than a year after the introduction of self-testing their place in the test strategy was evaluated. Methods We assessed trends in the number of self-tests sold, the number of positive self-tests reported, the proportion sold self-tests/total tests, and the proportion of all positive tests that were confirmed self-tests. To evaluate the reason why people use self-tests, we used the results of two online surveys among members of the general population: one among 27,397 people, held in April 2021, and one among 22,354 people, held in December 2021. Results The use of self-tests became substantial from end 2021 onwards. In the period mid-November 2021 - end-of-June 2022, the average proportion of reported sold self-tests to all COVID-19 tests was 37% and 14% of all positive tests were positive self-tests. In both surveys, the main reported reasons for using a self-test were having symptoms (34% of users in April 2021 and 31% in December 2021) and after a risk contact (27% in both April and December). Moreover, the number of self-tests sold, and the number of positive self-tests reported closely followed the same trend as the provider-administered tests in symptomatic people and high risk-contacts, which reinforces the hypothesis that they were mainly used for these two indications. Conclusions From end 2021 onwards, self-testing covered a significant part of COVID-19 testing in Belgium, which increased without doubt the testing coverage. However, the available data seem to indicate that self-testing was mostly used for indications outside of official recommendations. If and how this affected the control of the epidemic remains unknown.